Obtaining, encapsulation, and application of carotenoid-rich extract from guaraná peel (Paullinia cupana) - Pinho, Lorena Silva (2022)
The trends to upcycle by-products to alleviate the global concern related to population growth and food production expansion keep increasing. Although many strategies in waste management have been developed, it is worthwhile to valorize these by-products with low cost and minor environmental threats. In Brazil, with the biodiversity of the Amazon Region and the prosperous agribusiness, seeking new sources of bioactive compounds that possess economic and environmental merits is crucial. As most bioactive compounds are vulnerable to heat and oxygen, entrapping them into microparticles is a pre-requisite for food applications. Thus, the present study aimed to extract bioactive compounds from guaraná peel, a by-product from the agroindustry, and use them as core materials to develop microparticles that can be incorporated into functional products. In the first section of this work, characterization of the guaraná peels was investigated, including their compositions, such as the content of alkaloids, phenolic compounds, and carotenoids. The extraction conditions were also assessed to establish the optimal parameters for the recovery of pigments (β-carotene and lutein). Under the optimal conditions, the antioxidant capacity of the extracts was measured using in vitro assays. The results indicate guaraná by-products are excellent sources of carotenoids that possess a strong antioxidant capacity and likely bring health-promoting effects. However, as unstable natural pigments, carotenoids are highly susceptible to oxidation and isomerization after extraction. To increase their stability, in the second part of this work, the carotenoid-rich extract was encapsulated by spray drying (SD), chilling (SC), and their combination (SDC) to form microparticles. The physicochemical properties of the microparticles were explored, and their stability was evaluated during 90 days of storage. Scanning electron micrographs revealed spherical shape and size heterogeneity of samples. Moreover, the analysis of thermograms indicated that the carrier material and encapsulation process affect the thermal behavior of the microparticles. Similarly, water sorption data from the samples\' dynamic vapor sorption (DVS) mainly were related to the carrier agents used during encapsulation. Just a few studies approached whether encapsulation could protect the carotenoids under thermo-mechanical stress. Such information correlates with their application, as temperature and shear are mostly used during food production. Thus, the last part of this study conducted pasting processing to simulate the extrusion conditions and produce oatmeal paste enriched with microparticles loaded with carotenoids. After the processing, the influence of microparticles on the pasting properties of the oatmeal paste was evaluated. We found β-carotene retention was higher than those of lutein after treatment. Less severe conditions (temperature and shear) led to higher stability of the carotenoid. This study proposed that the encapsulation and application of carotenoids into food based on oat starch, which was processed at higher temperatures and shear, has the potential to develop functional products. However, incorporating new ingredients can affect the final products sensory properties and the bioactivity of mixed compounds. For this reason, future works specifically on the development of food products with desirable quality attributes and nutritional benefits are essential.